Experimental testing and numerical simulations for life prediction of gate valve O-rings exposed to mixed neutron and gamma fields. (15th October 2018) - Battini, D.; Donzella, G.; Avanzini, A.; Zenoni, A.; Ferrari, M.; Donzella, A.; Pandini, S.; Bignotti, F.; Andrighetto, A.; Monetti, A.
Abstract: EPDM O-rings of gate valves employed for the construction of a second-generation accelerator for the production of neutron-rich Radioactive Ion Beams were studied in order to assess their sealing performance both during the facility service time and the post-service storage phase. Several O-ring specimens were at first exposed to different dose levels of mixed neutron and gamma radiations. Correspondent modifications of physical and mechanical properties of the material were investigated by means of uniaxial tensile tests, dynamic mechanical analyses, aging, compression set and vacuum leak tests. A hyperelastic strain energy function was adopted to fit the mechanical response of the material as a function of the absorbed dose. The minimum squeeze degree that guarantees O-ring sealing efficiency at different irradiation levels was determined by varying the interference between O-rings and grooves. A finite element model of the vacuum leak test was then set up to assess the contact pressure level required to ensure sealing. Numerical simulations of the gate valve main O-ring were subsequently carried out. By comparison of the predicted contact pressure and strain levels with experimental results, a life prediction map, as function of the service time, the storage time and the O-ring squeeze degree, was proposed. Graphical abstract: Highlights: Study of mechanical properties evolution of EPDM irradiated with neutron and gamma mixed fields at different dose levels. Identification of structural and functional O-Ring end-points as function of the absorbed dose level (service time). Study of the sealing performance of the target chamber gate valve in a new generation radioactive ion beam source. Definition of gate valve O-Ring life prediction map as function of service time, storage time and squeeze degree.